Enchytraeidae (Oligochaeta, Annelida) from a field site in Portugal, with the description of five new species and a redescription of Enchylea heteroducta Nielsen & Christensen, 1963 - Schmelz, Rüdiger M.; Collado, Rut (Zootaxa, 2013)
Five new species of terrestrial Enchytraeidae (Oligochaeta, Clitellata) are described from an experimental field area in Portugal. Achaeta coimbrensis sp. nov. belongs to a group of species without pyriform glands and with lateral spermathecal ectal pores. Fridericia sousai sp. nov., F. roembkei sp. nov., F. marginata sp. nov., and F. ciliotheca sp. nov. have a maximum of four chaetae per bundle and two spermathecal diverticula, a character combination shared by c. 30 other species of this genus. The new Fridericia species are distinguished from these congeners by combinations of characters, but the ventral pattern of the clitellum alone is sufficient to separate the new species from each other. Enchylea heteroducta Nielsen & Christensen, 1963 is redescribed, this being the first record after the original description and the first record from a natural habitat. Further 16 species of enchytraeids are recorded, and there are now 32 species of enchytraeids known from Portugal.